COPING STRATEGIES FOR COMPLETING FINAL ASSIGNMENTS NOT ON TIME FOR COLLEGE STUDENTS WHILE WORKING IN THE BK STUDY PROGRAM PGRI UNIVERSITY BANYUWANGI (CASE STUDY): STRATEGI COPING PENYELESAIAN TUGAS AKHIR TIDAK TEPAT WAKTU PADA MAHASISWA KULIAH SAMBIL BEKERJA PRODI BK UNIVERSITAS PGRI BANYUWANGI (STUDI KASUS) - NUR KAMILASARI; Heriberthus wicaksono; Ahmad Sulthoni (Program Studi Bimbingan dan Konseling, 2023)
This research aims to find out what problems are faced by students who study while working and what coping strategies are applied in solving final assignment problems for students studying and working class of 2019, Guidance and Counseling Study Program, PGRI Banyuwangi University. This research is descriptive research with a qualitative approach. The research subject in this study was one person. The data collection technique uses the interview method. To obtain valid data in this research, in-depth interview techniques or methods were used. Test the validity of the data using triangulation techniques. The instrument in this research is an interview guide. Data were analyzed using the Milles and Huberman model with stages of data collection, data reduction, data presentation, and drawing conclusions.The results of the research show that the problems faced by students who study while working in completing their final assignments are: difficulty dividing time between study and work, difficulty dividing time with supervisors, and conditions that require making work a top priority. The coping strategy used by students is Planful Problem. accepted